E-PKKM as a Digital Quality Assurance Instrument - Vina Yunika Fitriani; Nur Inayah; Moh Sholihudin (Prodi PAI STIT Sunan Giri Bima, 2026)
This study aims to analyze the effectiveness of the implementation of e-PKKM (Electronic Madrasah Principal Performance Assessment) in order to support educational quality assurance at MTs. Miftahul Huda Ujungwatu Donorojo Jepara. Through a qualitative case study approach, this study explores the e-PKKM implementation process, supporting factors and obstacles, and its impact on improving madrasah principal performance and institutional quality. Data were obtained through in-depth interviews, participatory observation, and documentation review, which were then analyzed using the Miles and Huberman model. The results showed that the implementation of e-PKKM was quite effective, indicated by the fulfillment of assessment instrument components up to 90%, increased transparency and accountability, and strengthening of a data-driven work culture. The main supporting factors include the commitment of madrasah leaders, human resource readiness for technology, the availability of infrastructure, and mentoring from madrasah supervisors and the Jepara Ministry of Religious Affairs. However, a number of obstacles were still found, such as limited internet infrastructure, variations in digital literacy skills, high administrative burdens, and time constraints. Overall, e-PKKM made a significant contribution to improving data-driven management, academic supervision, and madrasah governance. This study recommends strengthening technical training, improving digital facilities, and administrative efficiency strategies to optimize the implementation of e-PKKM in the future.